Global health justice and governance - Ruger, Jennifer Prah (Oxford University Press, 2018)
In a world beset by extreme and unconscionable health disparities humankind desperately needs a new vision to ensure central health capabilities for all. This book lays out the profound health challenges facing the world today and offers a new theory of justice and governance as a way to resolve these seemingly intractable problems.